Biological activities of Usnea lethariiformis lichen extracts and UHPLC-ESI-QTOF-MS analysis of their secondary metabolites - Mauricio Piñeiro; Mauricio Piñeiro; Sofía Manrique; Jessica Gómez; Jessica Gómez; Juan Manuel Rodriguez; Patricia Barrera; Duilio Caballero; Miguel A. Sosa; Gabriel Vargas-Arana; Gabriel Vargas-Arana; Alejandro Tapia; et al. (Frontiers in Pharmacology)
This research was designed to investigate the metabolite profiling, phenolics content, and the trypanocidal, nematicidal, antibacterial, antifungal, and free radical scavenging properties of Usnea lethariiformis Motyka. The air-dried U. lethariiformis material was extracted successively with dichloromethane and methanol (UlMeOH). Two phases were obtained from the extract with dichloromethane, one soluble in methanol (UlDCM-s) and the other insoluble (UlDCM-i). The metabolite profiling was obtained using ultra-high-resolution liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UHPLC-ESI-QTOF-MS) system. The trypanocidal and nematicidal activities were determined according to standardized protocols. The antimicrobial activity was evaluated according to the Clinical and Laboratory Standards Institute (CLSI) rules. The total phenolic content of lichen extracts was determined by the Folin–Ciocalteu method. Antioxidant properties were assessed through 2,2-diphenyl-1-picrylhydrazyl (DPPH), Trolox equivalent antioxidant activity (TEAC), ferric-reducing antioxidant power (FRAP), and inhibition of lipid peroxidation in erythrocytes (ILP) assays, and the extracts exhibited robust antioxidant activity. Seventeen compounds were detected, of which thirteen were identified by UHPLC-ESI-QTOF-MS analysis, including depsides, depsidones, fatty acids, dibenzofurans, benzoic acids, and triterpenes. The UlDCM-s and UlMeOH extracts displayed strong trypanocidal activity against Trypanosoma cruzi epimastigotes at 50 μg/mL and 100 μg/mL and a nematicidal activity toward J2 Meloidogyne incognita, an important nematode infecting horticultural crops. Regarding the antimicrobial activity, the results showed that all bacteria and yeasts tested were inhibited by the different extracts with minimum inhibitory concentration (MIC) values between 25 μg/mL and 500 μg/mL. The UlDCM-s and UlMeOH extracts showed phenolic content of 107 mg and 48 mg gallic acid equivalents (GAE)/g dried extract, respectively. The UlDCM-s, UIDCM-i, and UlMeOH extracts showed moderate free radical scavenging activity in the DPPH, FRAP, and TEAC assays until 1 mg/mL and ILP tests at 250 μg/mL. The results indicated that U. lethariiformis may constitute a potential source of diverse bioactivities with application in the food, pharmaceutical, and agronomic industries.